Surgical treatment and reproductive outcomes in caesarean scar pregnancy at a single center - Yan Lei; Xin Du; Yu Liu; Fangshu Le; Jianshan Zhou (BMC, 2024)
Abstract Background To investigate factors associated with different reproductive outcomes in patients with Caesarean scar pregnancies (CSPs). Methods Between May 2017 and July 2022, 549 patients underwent ultrasound-guided uterine aspiration and laparoscopic scar repair at the Gynaecology Department of Hubei Maternal and Child Health Hospital. Ultrasound-guided uterine aspiration was performed in patients with type I and II CSPs, and laparoscopic scar repair was performed in patients with type III CSP. The reproductive outcomes of 100 patients with fertility needs were followed up and compared between the groups. Results Of 100 patients, 43% had live births (43/100), 19% had abortions (19/100), 38% had secondary infertility (38/100), 15% had recurrent CSPs (RCSPs) (15/100). The reproductive outcomes of patients with CSPs after surgical treatment were not correlated with age, body mass index, time of gestation, yields, abortions, Caesarean sections, length of hospital stay, weeks of menopause during treatment, maximum diameter of the gestational sac, thickness of the remaining muscle layer of the uterine scar, type of CSP, surgical method, uterine artery embolisation during treatment, major bleeding, or presence of uterine adhesions after surgery. Abortion after treatment was the only risk factor affecting RCSPs (odds ratio 11.25, 95% confidence interval, 3.302-38.325; P < 0.01) and it had a certain predictive value for RCSP occurrence (area under the curve, 0.741). Conclusions The recurrence probability of CSPs was low, and women with childbearing intentions after CSPs should be encouraged to become pregnant again. Abortion after CSP is a risk factor for RCSP. No significant difference in reproductive outcomes was observed between the patients who underwent ultrasound-guided uterine aspiration and those who underwent laparoscopic scar repair for CSP.